2018
DOI: 10.1155/2018/7515692
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer Effect of Honey in Nonsteroidal Anti‐Inflammatory Drugs Induced Gastric Ulcer Model in Rats: A Systematic Review

Abstract: Background Peptic ulcer is a basic term for ulcers on the lower oesophagus, stomach, or jejunum. The specific term for ulcer in the stomach is gastric ulcer. The extensive use of honey around the globe helps researchers to study the usefulness of honey. Many studies had already been conducted and proved the effectiveness of honey in treating gastric ulcer. Methods A systematic review of the literature was conducted to identify relevant studies on honey used as an alternative treatment of gastric ulcer cause by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…Nonetheless, the most commonly affected organs are the lesser curvature in the stomach and proximal duodenum, however, ulceration may also occur anywhere in the gastrointestinal tract (GIT) from pylorus to cardia. 2,3 Importantly, the prolonged use of NSAIDs is the second most common cause of PUD. 4 NSAIDs used for anti-inflammatory, antipyretic, pain-relief, anti-platelet aggregation, and anti-thrombogenesis indications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the most commonly affected organs are the lesser curvature in the stomach and proximal duodenum, however, ulceration may also occur anywhere in the gastrointestinal tract (GIT) from pylorus to cardia. 2,3 Importantly, the prolonged use of NSAIDs is the second most common cause of PUD. 4 NSAIDs used for anti-inflammatory, antipyretic, pain-relief, anti-platelet aggregation, and anti-thrombogenesis indications.…”
Section: Introductionmentioning
confidence: 99%
“…5 In particular, Indomethacin, an member of NSAIDs family, is widely used for the management of rheumatoid arthritis, several inflammatory diseases, and for its well-established cardiovascular protection properties; however, its contribution to gastric ulceration has been documented in literature. 2 The induced inhibition of the cyclooxygenase enzyme (COX-2) enzyme is responsible for indomethacin's anti-inflammatory effect. Nevertheless, when used to alleviate inflammation and pain, it is known to exert a severe damaging effect on epithelial cells of the digestive tract, which constitutes its serious side effect.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review identified by our scoping study was a biomedical research study from Malaysia, published in 2018. The aim was to “evaluate the therapeutic potential of honey in the context of its gastroprotective function against (non-steroidal anti-inflammatory drug)-induced gastric ulcers” in rats ( 24 ). Non-rat animal models were ineligible for this review, and the comparator group was required to be exposed to non-steroidal anti-inflammatory drugs.…”
Section: Resultsmentioning
confidence: 99%
“…It could have preferred to achieve the truest result with more animal groups, but the rule of Three Rs (Replacement, Reduction, and Refinement) emphasized in The Principles of Humane Experimental Techniques was the genuine indicator in this study (Kirk, ). Therefore, inspired by literature, only two different concentrations of each honey sample were used for the applying of animal experiments (Almasaudi et al, ; Fazalda, Quraisiah, & Nur Azlina, ; Nasuti, Gabbianelli, Falcioni, & Cantalamessa, ). It was well‐known that the goal of reduction was to reduce the numbers of animals used to obtain information about a given amount and precision.…”
Section: Discussionmentioning
confidence: 99%